PENGARUH PEMBERIAN PUPUK ORGANIK CAIR URIN SAPI FERMENTASI TERHADAP PERTUMBUHAN BIBIT SENGON (Paraserianthes falcataria L.) - Najmuddin Hamdie; Muhammad Muchtar Effendy; Ahmad Yamani (Universitas Lambung Mangkurat, 2021)
This study aims to determine the percentage of sengon seedling life, and determine the effect of the best concentration of liquid organic fermented cow urine fertilizer on the growth of sengon seedlings. The study used a completely randomized design with 5 treatments and 10 replications. The results obtained from this study are the percentage of live growth of Sengon seedlings by an average of 100%, the treatment has a significant effect on height increase and diameter increase while the effect of increasing number of leaves has no effect.Keywords: influence, organic, fermented cow urine, sengon